Impilikasi yuridis putusan pailit terhadap profesi notaris menurut peraturan perundang-undangan di Indonesia - Adheria Juniresta; Budi Santoso; Hanif Nur Widhiyanti (Jurnal Cakrawala Hukum, 2021)
This paper aims to understand the suitability of the regulations regarding the legalconsequences for notaries who are declared bankrupt. This type of normative legalresearch uses a statutory approach. Based on the results of the discussion, it was concluded that the provisions regarding legal consequences for notaries who weredeclared bankrupt in UUJN were specialist lex of similar provisions in the UUKand PKPU. This is also because the bankruptcy concept in UUJN is different fromthe bankruptcy concept in UUK and PKPU. Bankruptcy under UUK and PKPUoverrides the position of a person who is bankrupt, however bankruptcy in theUUJN may involve a person’s position as a Notary if the bankruptcy is the result ofan error committed by someone in his / her position as a Notary Public. Then thelegal consequence that can be accepted by a Notary who is declared bankrupt is thedismissal of his position as a Notary Public. Notaries can be sued for the fulfillmentof reimbursement of expenses, compensation or interest by the parties on the basis ofacts against the law. The bankruptcy regulation referred to in the UUJN is specificallyaimed at the notary’s position as a legal subject who represents a person andalso as a representative of his position who exercises the authority in making authenticdeeds.How to cite item: Juniresta, A., Santoso, B., Widhiyanti, HN. (2021). Impilikasi yuridis putusan pailit terhadap profesi notaris menurut peraturan perundang-undangan di Indonesia. Jurnal Cakrawala Hukum, 12(1), 1-10.doi:10.26905/idjch.v12i1.5783.